Bahasa Inggris - Maudina, Jeanita Seilia; Teguh Santoso, Made Panji; Marsingga, Prilla (Jurnal Ilmiah Wahana Pendidikan, 2025)
This article aims to analyze the role of Mekong Subregion countries in addressing the issue of human trafficking in Cambodia by applying the concept of human security. Human trafficking in Cambodia poses not only a serious threat to domestic security and stability but also has broader implications for international relations in the region. This research employs a descriptive qualitative method to examine the roles and policies of Mekong Subregion countries namely Thailand, Vietnam, Laos, and Myanmar in tackling human trafficking within the area. By using the human security concept, which emphasizes the protection of individuals from violence, exploitation, and systemic vulnerabilities, this study shifts the analytical focus from state-centered security approaches to the safety, rights, and dignity of individuals. The findings indicate that cooperation among Mekong Subregion countries plays a vital role in the prevention and suppression of human trafficking through coordinated cross-border operations, information sharing, and law enforcement capacity-building. Nonetheless, the study also highlights ongoing challenges, such as differing domestic policies, limited resources, and bureaucratic barriers. Despite these constraints, collective regional efforts have shown progress in addressing trafficking issues. The article concludes that enhancing cooperation and policy harmonization guided by a human security perspective is essential for achieving more effective and sustainable outcomes in combating human trafficking in Cambodia.